2002
DOI: 10.2134/jeq2002.5990
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and Spatial Variation of Episodic Wind Erosion in Unburned and Burned Semiarid Shrubland

Abstract: Redistribution of soil, nutrients, and contaminants is often driven by wind erosion in semiarid shrublands. Wind erosion depends on wind velocity (particularly during episodic, high-velocity winds) and on vegetation, which is generally sparse and spatially heterogeneous in semiarid ecosystems. Further, the vegetation cover can be rapidly and greatly altered due to disturbances, particularly fire. Few studies, however, have evaluated key temporal and spatial components of wind erosion with respect to (i) erosio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 69 publications
3
38
0
Order By: Relevance
“…More recently, fast‐response instruments to measure wind characteristics (e.g., sonic anemometers) are widely used to measure threshold shear velocity [ van Boxel et al , 2004]. These instruments can be deployed in the field along with active or passive dust aerosol samplers to investigate dust movement in the entrainment, transport, and deposition phases over large landscapes [ Whicker et al , 2002; Breshears et al , 2003; Mikami et al , 2006].…”
Section: Aeolian Research Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…More recently, fast‐response instruments to measure wind characteristics (e.g., sonic anemometers) are widely used to measure threshold shear velocity [ van Boxel et al , 2004]. These instruments can be deployed in the field along with active or passive dust aerosol samplers to investigate dust movement in the entrainment, transport, and deposition phases over large landscapes [ Whicker et al , 2002; Breshears et al , 2003; Mikami et al , 2006].…”
Section: Aeolian Research Methodsmentioning
confidence: 99%
“…Over time, the redistribution of soil from source to sink areas may reinforce patterns of wind and water erosion, leading to further degradation of source areas and additional enrichment of sink areas. Arid regions are particularly susceptible to increases in rates of wind and water erosion after disturbance such as fire or livestock grazing [ Whicker et al , 2002; Ludwig et al , 2005; Field et al , 2011] (see also section 4.5). For example, proxy records of dust deposition from high‐elevation lakes in the southwestern United States indicate that dust load levels have increased by 500% above the late Holocene average, likely due to land use change and disturbance associated with the expansion of livestock grazing in the early twentieth century [ Neff et al , 2008].…”
Section: Aeolian Processes: Impacts Interactions and Feedbacksmentioning
confidence: 99%
See 1 more Smart Citation
“…Dust emissions from travel on paved and unpaved roads are related to traffic characteristics and the quality of the road [ Etyemezian et al , 2003]. Windblown dust emissions generally occur over larger spatial scales and the magnitude of dust emissions during these events can eclipse the comparatively smaller, but more regular road dust emissions [ Okin and Gillette , 2001; Reynolds et al , 2001; Breshears and Allen , 2002; Whicker et al , 2002; Mahowald et al , 2007]. On a transcontinental scale, dust from regional wind storms in the Saharan and Chinese/Mongolian deserts can be transported across continents and impact areas in North America [ Prospero , 1999; VanCuren and Cahill , 2002; Darmenova et al , 2005].…”
Section: Introductionmentioning
confidence: 99%
“…There have been some observations but few measurements. Whicker et al (2002) undertook measurements near Carlsbad, New Mexico, and found that erosion was three times greater over several months and 70 times greater during strong winds for recently burned compared with unburned sites. Whicker et al (2002) undertook measurements near Carlsbad, New Mexico, and found that erosion was three times greater over several months and 70 times greater during strong winds for recently burned compared with unburned sites.…”
Section: Wind Erosionmentioning
confidence: 99%